Extended Model for Integrating Culture into Teaching EFL: A Context of Vietnam - Hoa, Chau Thi Hoang; Vien, Truong (Innovare Journal of Education, 2023)
Intercultural competence (IC) has gained a better positionality in English as a Foreign Language (EFL) education in Vietnam to enable young people to become effective global citizens. Accordingly, the development of comprehensive IC is considered to be an officially stated objective of the reformed EFL curriculum, and a great body of intercultural issues reflecting the cultural diversity of countries has been added to the English course books of the upper secondary level. To help EFL teachers with the exploitation of the coursebooks, this perspective paper aims to propose a model for Intercultural Language Learning and Teaching (IcLLT) to shed light on how to integrate culture into teaching EFL in a Vietnamese pedagogical teaching context. This model can be a valuable guideline for EFL teachers to go beyond the language skill-based lesson in order to promote learners’ intercultural communicative competence.